Generalizability in qualitative research: misunderstandings, opportunities and recommendations for the sport and exercise sciences - Smith, B. (Journal of Quantitative Analysis in Sports, 2018)
Generalisation in relation to qualitative research has rarely been discussed in-depth in sport and exercise psychology, the sociology of sport, sport coaching, or sport management journals. Often there is no mention of generalizability in qualitative studies. When generalizability is mentioned in sport and exercise science journals it is often talked about briefly or highlighted as a limitation/weakness of qualitative research. The purpose of this paper is to provide a detailed discussion of generalisation in order to dispel any misunderstandings or myths about generalizability in qualitative research and offer guidance about how researchers might consider generalisation. It is emphasised that it is a misunderstanding to claim that qualitative research lacks generalizability. It is highlighted that statistical types of generalizability that inform quantitative research are not applicable to judge the value of qualitative research or claim that it lacks generalizability. Reasons as to why researchers might consider generalizability in qualitative research are then offered. It is emphasised that generalisations can be made from qualitative research, but just not in the same way as quantitative results are. To help guide how generalisation might be considered, four different types of generalizability are presented: naturalistic generalisation, transferability, analytical generalizability and intersectional generalizability. Practical strategies are also offered for considering generalizability when seeking to publish qualitative research or reflect on already published work. The paper concludes with a set of recommendations to support high quality and rigorous qualitative research for scholars - including journal editors and reviewers - in relation to generalizability.